Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Menggunakan Metode TOPSIS Pada PT Avia Jaya Indah - Hertyana, Hylenarti; Fitria, Fitria; Rahmawati, Eva; Mufida, Elly (MEANS (Media Informasi Analisa dan Sistem), 2022)
PT Avia Jaya Indah has work targets that must be achieved in order to support the quality of the company. To achieve this work target, every employee must maximize his potential, so it is necessary to evaluate and evaluate employee performance. Facts in the field, to carry out employee performance appraisals are still carried out by task executors manually using an assessment form paper approved by the leadership. Performance appraisal is assessed based on subjectivity without clear and measurable standard criteria, resulting in gaps between employees. then there is a human error that is marked in making the calculation of the value so that it is less accurate, allowing errors to occur when calculating and formulating Excel formulas. The performance appraisal method in this study uses TOPSIS. The results of this study are to design and build an employee performance appraisal application system using the TOPSIS method.